Integrating Quantitative and Qualitative Methods in Patient Care Information System Evaluation - Stoop, A. P.; Berg, M. (Methods of Information in Medicine, 2003)
Objective: The aim of this paper is twofold. First, we describe two important dimensions of patient care information systems (PCIS) evaluation: the domain of evaluation and the different phases of the PCIS implementation. Second, we claim that, though Randomized Controlled Trials (RCTs) are often still seen as the standard approach, this type of design hardly generates relevant information for the organizational decision maker.Method: Interpretive study of evaluation literature. Results and Conclusions: The field of evaluation is scattered and the types of questions that can be asked and methods that can be used seem infinite and badly demarcated. Different stakeholders, moreover, often have different priorities in evaluating ICT. The most important reason for the lack of relevance of RCTs is that they are ill suited for investigating why and how a PCIS is being used, or not, and what the (often unplanned) effects and consequences are. Subsequently, our aim is to contribute to the discussion about the viability of qualitative versus quantitative methods in PCIS evaluation, by arguing for a specific integration of quantitative and qualitative research methods. The joint utilization of these methods, we claim, yields the richest results.
Keywords: Evaluation; multi-method approach; randomized controlled trial; patient care information system